TEMPERATURE DIAGNOSTICS OF GAS TURBINE ENGINE BEARINGS - R. V. Birukov; Y. V. Kiselev (Научный вестник МГТУ ГА, 2016)
The objective of the current research was to develop methodology for diagnosing industrial gas turbine engine bearings using the standard performance parameters. This paper presents mathematical thermal model of combined thrust and radial bearing and provides the model application examples for diagnostics.